2015
DOI: 10.3389/fpsyg.2015.01819
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Design Shapes Perceptual-motor Exploration, Learning, and Transfer in Climbing

Abstract: This study investigated how environmental design shapes perceptual-motor exploration, when meta-stable regions of performance are created. Here, we examined how creating meta-stable regions of performance could destabilize pre-existing skills, favoring greater exploration of performance environments, exemplified in this study by climbing surfaces. In this investigation we manipulated hold orientations on an indoor climbing wall to examine how nine climbers explored, learned, and transferred various trunk-rolli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(84 citation statements)
references
References 53 publications
1
83
0
Order By: Relevance
“…Nonetheless, anticipation tests need to delicately balance logistic constraints with the need to include variation of constraints in order to determine whether athletes can cope with variable visual-perceptual information. If they cannot, then variable constraints need to be included during anticipation training programmes in order to better prepare athletes for the variation in visual-perceptual information in the game setting (Seifert, Boulanger, Orth, & Davids, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, anticipation tests need to delicately balance logistic constraints with the need to include variation of constraints in order to determine whether athletes can cope with variable visual-perceptual information. If they cannot, then variable constraints need to be included during anticipation training programmes in order to better prepare athletes for the variation in visual-perceptual information in the game setting (Seifert, Boulanger, Orth, & Davids, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, athletic performance should be analysed on the ecological scale, which implies that the performerenvironment coupling is the smallest unit of analysis worth examining to understand sports performance and expertise (Ara ujo & Davids, 2018), otherwise defined as a complex adaptive system (i.e., a self-organising system, continuously regulating its behaviours without being regulated by an external regulator) (Davids, Ara ujo, Seifert, & Orth, 2015;Hendry et al, 2014;Seifert et al, 2017). For example, in rock climbing, we should be encouraged to view movement up the wall as the rolling motion of the body in reference to a surface of a climbing wall, rather than according to a longitudinal axis passing from the head to the feet of the climber (for more details, see Seifert et al, 2015).…”
Section: Key Concepts Of Ecological Dynamics Perspective To Expertisementioning
confidence: 99%
“…Engagement in exploratory actions is thought to be critical for the acquisition of perceptual-motor control (Adolph, Eppler, Marin, Weise, & Clearfield, 2000) as this supports the attunement of actions to changing properties of the environment (Reed, 1996). For example, in a recent climbing study, Seifert and colleagues revealed that behavioral exploration during practice led to increased climbing fluency in a transfer test (Seifert, Boulanger, Orth, & Davids, 2015).…”
mentioning
confidence: 99%